Surface charge properties and others soil characteristics in Shamil-Ashkara catchment, Iran - Moghimi, Abolhassan (2012)
Iran is one of the countries with most parts affected by arid condition (> 90%) with accumulation of calcareous materials in some soils as well as salt in some others. There is no reported study showing the relation between soil characteristics and aggregate stability in southeast Iran and study on surface charge properties and relationship between soil characteristics and surface charge in arid regions. The stability of soil aggregates in this area is deteriorating due to intensive agriculture practices, land use change, low organic matter content, high content of sodium and groundwater saline water. This study outlines principal characteristics of soils that occur in the arid region of southeastern Iran and deems significant, as the data obtained will provide empirical information concerning the effect of minerals and soil properties on the aggregate stability and surface charge characteristics of soils in this catchment. The objectives of this study were (I) to identify the major physico-chemical and mineralogical properties of the soil of southeastern Iran and (II) to appraise their effects on the clay dispersion and surface charge characteristics of these arid soils. To attain these objectives, eight soils representing areas of the alluvial plain and the colluvial fan sediments along the slope area in Shamil-Ashkara catchment, Iran, were investigated. The soils were internationally classified using the criteria of Soil Taxonomy (Soil Survey Staff, 2010) and the FAO (2007) world reference base for soil resources. They are in the recent stage of development. They were identified as 1 calcic haplosalids, 3 aridic ustorthents and 4 aridic ustifluvents. The soils are calcareous and alkaline. The soils physico-chemical properties do not show any clear trend with depth. The results assent with the nature of alluvial and colluvial deposition that varies from time to time. All soils have pH values above 7 and the electrical conductivity (EC) vary from slightly saline to saline. The organic carbon content was low in all soils, which is common for soils of these regions where the vegetation is strongly influenced by the climatic conditions. The soils tend to be massive when the silt content is high, otherwise the structure would be single grain when the sand content is high, resulting in their weak and structurally unstable properties. The major minerals present in the parent material samples are Chlorite, illite,smectite, kaolinite, palygorskite, feldspars, quartz, calcite and interstratified illitesmectite.In the soil, the common minerals are quartz, feldspars, smectite,palygorskite, chlorite, illite, kaolinite and sepiolite. Arid soils are structurally unstable and disperse easily in water. Soil pH affects stability aggregates the most as indicated by high significant correlation between pH and water-dispersible clay (WDC) (r = 0.78**). There is the highest positive significant correlation between soil EC and WDC (r = 0.95**). Multiple linear regression analysis also indicated that EC has the highest influence on WDC. Among the minerals present, palygorskite significantly influences the WDC (r = 0.70**) the most, while chlorite has the least significant effect. The results indicated that the significant positive factors affecting WDC are in the order of electrical conductivity (EC) >pH > permanent negative charge (Qp) > K+ >CEC > Na+ >palygorskite > SAR > Mg2+ >clay content. Soil surface charge characteristics also affect soil minerals and properties. The point of zero charge (pH0) is one of the most important parameters used to describe variable-charge surfaces. The results indicated that PZC values are low (2.8 – 3.37) in all samples and lower at the surface than in subsurface horizons. There is a positive significant correlation between pH0 values, organic carbon percentage and crystalline Fe (Fed). The points of zero net charge (PZNC) values are low (< 2) in the pedons studied, which refers to large amounts of negative charge in these soils. The permanent charge (Qp) of the soils studied is also large and negative, which agrees with the amount of clay and the mineralogy of these soils. There is a positive significant correlation between Qp and WDC, clay content, palygorskite, CEC, OC, Fed, Mg, Na, pH, SAR. The highest positive correlation was recorded between Qp and WDC (r = 0.78**).